On the systemic approach to balance deficiency: Systemowe podejście do zaburzeń równowagi - Kowalska-Napora, Ewa (Management and Administration Journal, 2021)
Any system, seen as a compound issue, is subject to various forms of disturbance which are later eliminated in systemic relaxation time. While assessing the course of changes and the degree of elimination it is necessary to identify the time layers as well as the quantification of the features used to describe the n-dimensional space. What needs to be defined is firstly, the number of dimensions, i.e. a reference to the non-Euclidean space and, secondly, an attempt to define this space with the help of non-parametric features, i.e. non-quantified in the non-parametric distribution. The aim of the work performed by its Author is to define ways of describing relaxation time in non-parametric space.